Parabolic trough solar receivers characterization using specific test bench for transmittance, absorptance and heat loss simultaneous measurement. (15th October 2016) - Navarro-Hermoso, J.L.; Espinosa-Rueda, G.; Heras, C.; Salinas, I.; Martinez, N.; Gallas, M.
Highlights: Laboratory test bench for the thermal and optical evaluation of PT solar receivers. Optical spectral measurement of transmittance and reflectance from 300 to 2500 nm. Evaluation of the selective coating at temperatures up to 450 °C. Heat losses measurement at temperatures up to 650 °C by uniform Joule heating. Evaluation of receivers with different diameter. Antireflective coating analysis. Abstract: Parabolic trough is the most extended solar thermoelectric technology. Solar radiation is converted into heat and transferred to the heat transfer fluid in the solar receiver tubes. The thermal energy obtained feeds a conventional Rankine power cycle. The performance of the receiver tube can be broken down into three single components: the optical transmittance of the outer glass envelope or capability in transmitting the radiant energy; the optical absorptance of the metal tube or capability to absorb the radiation; and heat losses of the tube or capability to retain the heat which depends of inner tube coating emissivity and the vacuum between both tubes. In this paper a novel test bench implementing both thermal and optical measurement systems is described and compared with other systems referred in the literature. The results obtained from the evaluation of three different solar receivers with different diameters are presented. Optical measurements of transmittance and absorptance parameters are carried out in the wavelength range of 300–2500 nm. Optical evaluation of trough receivers at operating temperatures up to 450 °C is feasible. The receivers can be heated using a high intensity electric current flowing through the internal tube. Uniform Joule heating results a reliable heat losses measurement method at temperatures up to 650 °C.